Sports tourism and sports events as a niche market in Oporto as a tourism destination - Liberato, Pedro (2020)
Football is experienced in a much more intense way compared to other sports, which is also why it has a relevant place in society, when compared to other sports activities. The general objective of this research study is to ascertain the importance and perception of FC Porto regarding the ability to influence the main activities performed during the trip. Considering the general objective, an hypothesis was proposed: The importance and perception of FC Porto in Porto as a destination, influence the main activities carried out during the trip. Visioning the research objective, a quantitative methodology was applied through the application of a questionnaire to 400 tourists/visitors in the city of Oporto. Considering the results, regional and local DMO’s are suggested to promote programs that guarantee complementary offer at the destination, coincident with sporting events, in order to ensure the extension of the stay.